Bir Oktilfenol Polietoksilatın Persülfat İle Aktive Edilmiş Sıfır Değerlikli Demir Nanopartikülleri İle İleri Oksidasyonu Ve Toksik Etkisindeki Değişim - Temiz, Kübra (Fen Bilimleri Enstitüsü, 2015)
Biyokimyasal olarak zor ayrışan, arıtmaya karşı dirençli, toksik ve/veya mutajenik etkileri olan bazı endüstriyel kirleticilerin su kaynaklarımızdaki varlığı ekosistemleri tehdit etmektedir. Endokrin bozucu özellikleri olduğu bilinen ve noniyonik yüzey aktif maddelerin bileşiminde bulunan alkil fenol polietoksilat metabolitlerinin konvansiyonel fiziksel, biyolojik ve kimyasal arıtma yöntemleri ile giderimleri yetersiz kalmaktadır. Bu nedenle alkil fenol polietoksilatların ve alkil fenollerin ileri oksidasyon prosesleri gibi ileri arıtma yöntemleri ile giderim çalışmaları ve uygulamaları son yıllarda önem kazanmıştır. İleri oksidasyon prosesleri arasında hızları ve yüksek giderim verimleri nedeniyle Fenton, Fenton-benzeri ve Foto-Fenton proseslerinin atıksu ve su arıtımında sorunlu kirleticilerin oksidasyonu için tercih edilmektedir. Son yıllarda ekonomik, kolay uygulanabilir ve etkin olması nedeniyle hidrojen peroksit ve persülfat gibi oksidanlarla aktive edilebilen sıfır değerlikli demir ile arıtma prosesleri dikkat çekmektedir.   Yukarıdaki bilgiler ışığında bu tez kapsamında, bir oktil fenol polietoksilat bileşiği olan noniyonik bir yüzey aktif maddenin (ticari ismi: Triton X-45), persülfat (S2O82-) iyonları ile aktive edilmiş sıfır değerlikli demir kullanılarak arıtımı incelenmiştir.Yüzey aktif maddenin Persülfat/Sıfır değerlikli demir ileri oksidasyon sistemi ile arıtılabilirliği üç aşamada çalışılmıştır. Birinci aşamada, prosesi etkileyen parametrelerin (katalizör konsantrayonu, oksidan konsantrasyonu, pH, arıtma süresi) oksidasyon verimi üzerindeki etkileri araştırılmış, yüzey aktif madde (20 mg/L sulu çözelti) ve TOK giderimi bazında optimize edilmiştir. En uygun pH değeri 5, optimum persülfat konsantrasyonu 2.5 mM, optimum katalizör konsantrasyonu 1 g/L, optimum arıtma süresi 60 dk. olarak belirlenmiştir. Çalışmanın ikinci aşamasında arıtma sisteminin ekotoksikolojik etkilerini incelemek üzere seçilen deneysel koşullarda arıtılmış numunelerde akut toksisite testleri gerçekleştirilmiştir. Toksisite biyodeneylerinde test organizmaları olarak Vibrio fischeri fotobakterileri ve bir tatlısu mikroalgi olan Pseudokirchneriella subcapitata kullanılmıştır. Yapılan deneysel çalışmalar neticesinde, belirlenen en uygun arıtma koşullarında OPEO’ nun % 95 TOK’un ise %40 oranında giderimi sağlanmıştır. Vibrio fischeri ve Pseudokirchneriella subcapitata ile yürütülen akut toksisite deneyleri ile 120 dakikalık reaksiyon süresi sonucunda % bağıl toksisite değerleri Vibrio fischeri için %66’dan %20’ye düşürülmüş, Pseudokirchneriella subcapitata için ise %16 olan bağıl toksisite tamamen giderilmiştir.

Surfactants are organic chemicals that reduce surface tension in water and other liquids. The most familiar use for surfactants are soaps, laundry detergents, dishwashing liquids and shampoos. They are a diverse group of chemicals with unique cleaning and/or solubilisation properties. They usually consist of a polar (hydrophilic) and a nonpolar (hydrophobic) group. Due to their amphiphilic nature they are widely used in household cleaning agents (detergents), personal care products, textiles, paints, inks, polymers, pesticide formulations, pharmaceuticals, mining, oil recovery as well as pulp and paper industries. Surfactants enter the environment mainly through the discharge of sewage effluents into natural water and the application sewage sludge on land for soil fertilizing purposes. Most of the commercial surfactants used today by different industries are only partially and slowly biodegradable; they tend to sorb and accumulate on sludge and soil  sediments.causing a potential ecotoxicological and pollution risk in the environment. Moreover, the metabolites of some alkyl phenol ethoxylates have recently been declared as hormone mimicking/endocrine disrupting compounds. Therefore, the efficient management and treatment of surfactants remains a serious challenge. In this respect, more effective and at the same time economically feasible abatement processes have to be developed to alleviate the problem of surfactants/surfactant metabolites in the environment. Alkylphenol polyethoxylates are industrial compounds belonging to the class of nonionic surfactants that are designed to have both hydrophilic and hydrophobic properties. Among them, octylphenol polyethoxylates have been widely used in cleaning products, paints, ink dispersants, textile preparation and leather processing, manufacture of pulp and paper, metalworking, cosmetics and personal care products. However, many of these applications are now restricted by the European Commission due to the raising concerns regarding the environmental safety of alkylphenol (poly)ethoxylates and its metabolites. It has been reported that their aerobic / anaerobic transformation products (alkylphenols such as nonylphenol and octylphenol) are much more inhibitory and estrogenic than the original surfactants. Despite the above-mentioned concerns regarding the use of alkylphenol (poly)ethoxylates, these products still appear in several industrial applications where they cannot not be replaced by alternative chemicals due to technical and economic reasons. Consequently, the presence of these nonionic surfactants and their degradation products have been reported in water bodies, sediments and sludge associated with the continuing discharges from industrial and sewage treatment plants.  The scientific literature on the biodergadability and fate of alkylphenol polyethoxylates in the aquatic as well as terrestrial environment reinforces the idea that more efficient, alternative treatment processes are needed for their effective elimination. Besides conventional biochemical, chemical and physical treatment methods, chemical oxidation (ozonation, advanced oxidation) has been extensively studied as an alternative for the treatment of nonionic surfactants and their metabolites. Among the existing hydroxyl radicals (HO•)-induced advanced oxidation processes, TiO2/UV, H2O2/UV, O3/UV, H2O2/UV, Fenton and Photo-Fenton processes have attracted considerable interest since these exhibit relatively high treatment efficiencies and kinetics. More recently, sulfate radicals (SO4•-)-driven advanced oxidation processes have been investigated to treat pollutants found in water and wastewater. The reduction potential of SO4•- is lower than that of HO• (2.6 versus 2.9 eV); however, SO4•- are also capable of non-selectively and rapidly reacting with pollutants in a series of free radical chain reactions being similar to those established for HO•-based advanced oxidation processes. SO4•- can be produced from persulfate ions via chemical, radiolytic, thermal or photochemical activation; or alternatively by redox reactions with transition metals as in the case of the Fenton’s reagent. An alternative to iron-based (Fenton-like) advanced oxidation processes are zero valent iron (ZVI; Fe0) catalyzed treatment systems. They have received global interest and promising results have been reported so far for the removal of chlorinated organics, nitroaromatic compounds, arsenic, heavy metals, nitrate, industrial dyes and phenols by micro-and nanoscale ZVI. ZVI is reactive (redox potential = - 0.44 eV), non-toxic, abundant, cheap, relatively easy to produce and its treatment applications require little maintenance. ZVI is capable of oxidizing organic as well as inorganic pollutants by an electron transfer mechanism. However, for harsher conditions, ZVI treatment has to be enhanced chemical or thermally by the involvement of oxidants (for example, hydrogen peroxide or persulfate). Besides, the extensive follow-up of toxicity is critical to ensure economically and ecologically safe applications of advanced oxidation processes. The ecotoxicological characterization of sulfate radical-based treatment systems during their application to treat industrial pollutants is an untouched area in this research field. For this purpose, bioassays employing the marine photobacterium Vibrio fischeri remain the most popular test protocols since these enable easy and rapid measurement of cytotoxicity in water and wastewater samples being subjected to advanced oxidation. Although V. fischeri is very sensitive and hence useful for obtaining a preliminary idea about the inhibitory effect of pollutants and their degradation products, it is more appropriate to support toxicity results with other types of test organisms preferably from different trophic levels. For example, Pseudokirchneriella subcapitata are important freshwater microalage being routinely used as primary producers ito assess the acute and chronic toxicity of surfactants.  Considering the above facts, the motivation of the present work was to study the treatability and acute toxicity of the commercially important nonionic surfactant octylphenol polyethoxylate (known as “Triton X-45”) in aqueous solution with the ZVI/S2O82- advanced oxidation system. To our knowledge, this was the first study investigating the treatability of a nonionic surfactant with persulfate activated ZVI nanoparticles. Within the scope of this experimental study, firstly, preliminary optimization tests were performed under varying reaction conditions (ZVI and persulfate concentrations, pH’s and treatment time) together with control runs (ZVI only and persulfte only expeirments). Thereafter, time dependent changes in the surfactant, TOC, persulfate concentrations and pH were followed for the optimized treatment system. Then, the acute toxicity of the nonionic surfactant and its degradation products was also followed by employing two different bioassays with V.fischeri and P. subcapitata. It can be said that, OPEO has corrosive and toxic effects on people and other organisms. Results indicated that the nonionic surfactant solution (20 mg/L original concentration) could be degraded in less than 1 hour (40-60) by 95% accompanied with up to 40% TOC removal by 1 g/L ZVI nanoparticles activated with 2.5 mM (480 mg/L) persulfate at an initial reaction pH of 5.0. The acute toxicities (percent relative inhibition rates) decreased significantly from originally 66% to 21% and originally 16% to non-toxic for V.fischeri and P. subcapitata, respectively. The photobacterium V.fischeri appeared to be more sensitive to octylphenol polyethoxylate and its degradation products than the microalgae P. subcapitata.
Advanced Oxidation Of An Octylphenol Polyethoxylate With Persulfate Activated Zero Valent Iron Nanoparticles And Changes In Its Toxic Effect
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Oktilfenol; Polietoksilat; Persülfat; Sıfır; Değerlikli; Demir; Sdd; Ps; İleri; Oksidasyon; Toksisite; Advanced; Oxidation; Octylphenol; Polyethoxylate; Persulfate; Zero; Valent; Iron; Zvi; Toxicitiy